Plant Stress Physiology 2021
DOI: 10.5772/intechopen.91971
|View full text |Cite
|
Sign up to set email alerts
|

Role of Plant Carbonic Anhydrases under Stress Conditions

Abstract: Carbonic anhydrases (CAs) are enzymes catalyzing the reversible hydration of carbon dioxide with the generation of protons and bicarbonate. The components of the reaction are involved in almost all metabolic processes in higher plants and algae, maintaining the balance of electrolytes and pH, gluconeogenesis, lipogenesis, ethylene synthesis, and others. The CAs may take part in transmitting signals to activate cascades of protective response genes. Our findings reveal significant changes in the content of carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 142 publications
(186 reference statements)
2
1
0
Order By: Relevance
“…The D. viscosa contains phenols and polyphenols having the capability to act as carbonic anhydrase inhibitors; thus, our findings agree with the data stated by Karioti et al [67]. The current finding presented that our data do not match with the data recorded by Rudenko et al [68] because environmental stress influences the quality and quantity of bioactive ingredients responsible for numerous biological activities. Furthermore, the MeOH extract of J. excelsa followed by the EtOAc fraction of J. excelsa displayed significant potential an IC 50 = 5:1 ± 0:20 and IC 50 = 38:4 ± 2:52 μg/mL significance in comparison to other tested fractions.…”
Section: Antidiabetic Significancesupporting
confidence: 75%
“…The D. viscosa contains phenols and polyphenols having the capability to act as carbonic anhydrase inhibitors; thus, our findings agree with the data stated by Karioti et al [67]. The current finding presented that our data do not match with the data recorded by Rudenko et al [68] because environmental stress influences the quality and quantity of bioactive ingredients responsible for numerous biological activities. Furthermore, the MeOH extract of J. excelsa followed by the EtOAc fraction of J. excelsa displayed significant potential an IC 50 = 5:1 ± 0:20 and IC 50 = 38:4 ± 2:52 μg/mL significance in comparison to other tested fractions.…”
Section: Antidiabetic Significancesupporting
confidence: 75%
“…In the present study, genes related to NAD (P)H, such as NADH-dependent glutamate synthase, NAD(P)H-quinone oxidoreductase subunit 4, NADH dehydrogenase (ubiquinone) Fe-S protein, NADH:quinone reductase, and NADHubiquinone oxidoreductase, showed significant up-regulation in resistant genotypes, confirming its role in energy homeostasis in plants under stress conditions. Other than NADH-related genes, shoot transcriptome data of resistant genotypes in the present study also showed significant up-regulation of other genes involved in energy metabolism, such as phosphoenolpyruvate carboxylase (Wang et al, 2016;Waseem and Ahmad, 2019), alcohol dehydrogenase (Su et al, 2020), alanine transaminase (Bashar et al, 2020), ATP citrate (pro-S)-lyase (Liu F. et al, 2022), ATPase , carbonic anhydrase (Rudenko et al, 2021), cytochrome c, cytochrome c oxidase (Guerra-Castellano et al, 2018;Analin et al, 2020), fructose-bisphosphate aldolase (Lv et al, 2017;Cai et al, 2022), malate dehydrogenase (Song et al, 2022), 6-phosphofructokinase 1 (Wang H. et al, 2021), photosystem II P680 reaction center D1 protein (Landi and Guidi, 2022), phosphoserine aminotransferase (Wang et al, 2022), pyruvate-orthophosphate dikinase (Yadav et al, 2020), and serine O-acetyltransferase (Mulet et al, 2004;Liu D. et al, 2022), and their molecular mechanism and role in energy homeostasis in different crops is well reviewed. It indicates that the significant up-regulation of the genes involved in energy metabolism in KWR 108 might have helped it to cope with Fusarium wilt stress by maintaining energy homeostasis in cells under stress conditions.…”
Section: Significant Up-regulation Of Energy Metabolism Genes In the ...supporting
confidence: 55%
“…Moreover, carbonic anhydrases (CAs) are a class of Zn-containing enzymes that catalyze the reversible hydration of carbon dioxide while producing protons and bicarbonate that are involved in several metabolic processes in different plant species. Furthermore, the CAs play an essential role in photosynthesis in both C3 and C4 plants, signaling, activation of several protective response genes, and protection of crop plants in response to several stress conditions including high illumination, low and high concentration of carbon dioxide, drought, and salinity [66][67][68].…”
Section: Putative Tissue Expression Pattern Subcellular Localization ...mentioning
confidence: 99%